2020
DOI: 10.1007/s00394-020-02345-7
|View full text |Cite
|
Sign up to set email alerts
|

Egg consumption and cardiovascular risk: a dose–response meta-analysis of prospective cohort studies

Abstract: Purpose Cardiovascular disease (CVD) is a leading cause of mortality globally and is strongly influenced by dietary risk factors. The aim was to assess the association between egg consumption and risk of CVD risk/mortality, including coronary heart disease (CHD), stroke, and heart failure. Methods MEDLINE, Embase, and Web of Science databases were searched through April 2020 for prospective studies. Two independent reviewers screened and extracted the data through standardized methods. Size effects were calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 82 publications
1
42
0
2
Order By: Relevance
“…Recently, a dose-response meta-analysis of prospective cohort studies found no association with risk of cardiovascular outcomes following the habitual consumption of one egg per day compared to no intake, with exception of the risk of heart failure, which resulted higher especially in men from US cohorts [36].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a dose-response meta-analysis of prospective cohort studies found no association with risk of cardiovascular outcomes following the habitual consumption of one egg per day compared to no intake, with exception of the risk of heart failure, which resulted higher especially in men from US cohorts [36].…”
Section: Discussionmentioning
confidence: 99%
“…Although a review of the observational studies concluded no significant associations of egg consumption with some health outcomes, such as cancer, CVD, and metabolic diseases, they observed a protective relationship between egg consumption and stroke risk (8). A recent meta-analysis also showed an inverse association of up to 6 eggs/wk consumption with CVD incidence and/or mortality (9). Among the US population, they observed a lower risk of CVD for 4 eggs/wk [relative risk (RR) (95%): 0.94 (0.89-0.99), I 2 (%) = 20].…”
Section: Introductionmentioning
confidence: 99%
“…18 Moreover, confounding the issue, inconsistent and sometimes conflicting results have been reported regarding the potential health risks of egg consumption. [19][20][21][22] The present study assessed the effect of whole egg consumption on cognitive functioning among US older adults. It contributed to the literature in three aspects.…”
Section: Introductionmentioning
confidence: 99%
“…Limitations of the existing studies include crude daily egg intake measures (e.g., by a single question item or food frequency questionnaire) and lack of US‐based studies (only one based on our literature search) 18 . Moreover, confounding the issue, inconsistent and sometimes conflicting results have been reported regarding the potential health risks of egg consumption 19–22 …”
Section: Introductionmentioning
confidence: 99%